News of the world [videorecording (DVD)] - Greengrass, Paul; Greengrass, Paul; Hanks, Tom; Marvel, Elizabeth; McKinnon, Ray; Jiles, Paulette, 1943- (Universal Pictures Home Entertainment, 2021)
In the aftermath of the Civil War, Captain Jefferson Kyle Kidd, an elderly widower and itinerant news reader, is offered fifty dollars to bring an orphan girl, who was kidnapped and raised by Kiowa raiders, from Wichita Falls back to her family in San Antonio.